EVALUASI SENSORI SUSU FERMENTASI PROBIOTIK YANG DIINOKULASI Lactobacillus casei subsp. casei R-68 DENGAN VARIASI PENAMBAHAN SUKROSA - Handayani, Tiara Githasari; Pato, Usman; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The addition of sucrose for productionof milk fermented is expected to affect the sensory quality of probiotic fermented milk produced. Lactobacillus casei subsp. caseiR-68 is probiotic bacteria isolated from dadih. This study useda Completely Randomized Design (CRD) with 4 treatments and 4 replications thus obtaining obtain 16 experimental units.Data yang diperoleh dianalisis secara statistik dengan menggunakan analisis sidik ragam (ANOVA).The data obtained were statistically analyzed using Analysis of Variance (ANOVA).Jika F hitung lebih besar atau sama dengan F tabel maka dilanjutkan dengan uji DNMRT pada taraf 5%. If the  F count is greater than or equal to F table then continued with DNMRT test at 5% level.The results show that the addition of sucrose significantly affected the taste and consistency, but did not significantly influence the color of probiotic fermented milk. Overall acceptance test indicated that the panelists were“rather like to like”forprobiotik fermented milk. The best treatment based on the sensory evaluation was treatment S2 (addition 5% concentration of sucrose).   Keywords: Fermentation, Lactobacillus casei subsp. caseiR-68 and Sucrose.